2016
DOI: 10.1007/978-3-319-19671-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Helping Another in Distress: Lessons from Rats

Abstract: Every man must decide whether he will walk in the light of creative altruism or the darkness of destructive selfi shness. This is the judgment. Life's most persistent and urgent question is, What are you doing for others?As a neurobiologist, I was somewhat surprised, but also thrilled, to receive an invitation to Oakland University's Evolution of Morality conference. I was surprised because I work with rats. Although I think very highly of rats, I also recognize reality. Morality is a stretch for members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Those studies demonstrated that social factors may dominate the desire for preferred food in rats. Furthermore, it was argued that rats perform prosocial behavior toward both familiar and unfamiliar rats, and that such performance is repeated consistently and intentionally day after day and at shorter and shorter latencies [ 15 ]. It was also suggested that social animals have evolved strong innate preferences for cooperative behavior [ 22 ], and that a specific behavior is not a mere product of the proximal immediate cost and benefit, but it also has an ancestral component, balancing the gain in an ultimate evolutionary success in addition to the immediate gain [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Those studies demonstrated that social factors may dominate the desire for preferred food in rats. Furthermore, it was argued that rats perform prosocial behavior toward both familiar and unfamiliar rats, and that such performance is repeated consistently and intentionally day after day and at shorter and shorter latencies [ 15 ]. It was also suggested that social animals have evolved strong innate preferences for cooperative behavior [ 22 ], and that a specific behavior is not a mere product of the proximal immediate cost and benefit, but it also has an ancestral component, balancing the gain in an ultimate evolutionary success in addition to the immediate gain [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is oriented toward and beneficial for others (Mason, 2021). Helping behaviors are intentional by definition, and those behaviors that are unintentional but beneficial to others does not fit into this category (Mason, 2016). Helping behaviors can be instrumental or emotional (Bamberger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%